Teaching the lexicology in the course of the Ukrainian as a foreign language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the peculiarities of lexicology coherence during the process of studying the Ukrainian as a foreign language; the linguistic, psychological and lingvodidactic criteria of enriching the vocabulary of foreign students are considered as well.
Keywords: the Ukrainian as a foreign language; studying the lexicology; linguistic basis; psychological criteria; onosemasiology